In vitro epidermis model mimicking IGF‐1–specific age‐related decline. Issue 5 (6th June 2018) - Mainzer, Carine; Remoué, Noëlle; Molinari, Jennifer; Rousselle, Patricia; Barricchello, Carla; Lago, Juliana C.; Sommer, Pascal; Sigaudo‐Roussel, Dominique; Debret, Romain
Abstract: Ageing is a complex multifaceted process affecting skin functionality and structure. Several 3D organotypic skin culture models have reproduced ageing by inducing replicative senescence, glycation or oxidative stress. Yet, very few models have focused on hormonal ageing and especially the insulin‐like growth factor 1 (IGF‐1) signalling pathway, which has been associated with longevity in animal studies and is necessary for the early stages of skin development. In this study, we built an organotypic epidermis model with targeted IGF‐1 receptor knockdown to reproduce some aspects of hormonal ageing on skin. Our model displayed morphological and functional features of aged epidermis, which were mostly attributed to a loss of function of the S tratum basale . IGF‐1 receptor knockdown keratinocytes depicted an extended cell cycle, reduced proliferation potential and reduced adhesion capacities and greater sensitivity to oxidative stress than control cells. Altogether, this model represents an essential tool for further investigations into the mechanisms linked to some aspects of hormonal decline or when screening for potent anti‐ageing compounds.